(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article deals with the development of listening comprehension skills in English language learners, focusing on the integration of lingvodidactic and psycholinguistic principles. In the context of globalization and the increasing importance of English as a lingua franca, effective listening comprehension is crucial for language learners. The research draws on the works of prominent scholars such as I.A. Zimnyaya, D. Singleton, and L. Ryan, alongside methodological contributions from Sh.X. Akbarova, N.D. Galskova, and Z.N. Nikitenko. Employing a mixed-methods approach, the study combines a literature review with a survey of 100 English language teachers in Uzbekistan. Key findings highlight the importance of authenticity and content relevance, activity-based learning, differentiation, motivation, consistency, and the integration of listening with other language skills. Despite recognizing these principles, teachers face challenges such as limited access to authentic materials, insufficient training, and time constraints. The study underscores the need for modern teaching methodologies, personalized instruction, and the use of authentic materials to create an engaging and effective learning environment. The findings offer valuable insights for educators and policymakers, emphasizing the importance of addressing these challenges to enhance listening comprehension skills in English language learners. Future research should focus on practical strategies for overcoming these barriers, particularly in resource-limited settings.